Maltreatment and depression among left-behind adolescents in rural China: The moderating roles of food security and depression literacy. (April 2021) - Yang, Fan; Shen, Yang; Nehring, Daniel
Abstract: Background: Maltreatment is a leading cause of adolescent depression. Economic empowerment and mental health services provision are major policy options to solve this problem in developing countries. However, little is known about how these policy options jointly influence the association between maltreatment and adolescent depression. Objective: To examine how the configuration of food security and depression literacy influenced the association between maltreatment and depression of Chinese rural left-behind adolescents (LBAs). Participants: The analysis was based on the responses of 1, 469 LBAs (12–18 years old) from 21 rural schools in 2018. Methods: The participants responded to items on the Birleson Depression Self-Rating Scale, the Childhood Trauma Questionnaire, the Food Insecurity Experience Scale, a clinical vignette on depression, and questions on their demographic information. The data was analyzed using a hierarchical moderated regression model. Results: Maltreatment was significantly associated with depression of LBAs ( p < .001). The independent moderating effect of food insecurity ( p < .05) or of depression literacy ( p < .05) was observed only after including the interaction of maltreatment, food insecurity, and depression literacy. The configuration of food insecurity and depression literacy significantly moderated the focal association ( p < .05). Specifically, in the low food insecurity setting, low depression literacy significantly strengthened the focal association ( p < .01), while in the high food insecurity setting, high depression literacy significantly strengthened the focal association ( p < .01). Conclusions: Depression interventions for adolescents in under-resourced communities should consider both food security and psychoeducation, and the implementation of the latter should be based on the level of the former.